The adoption of vendor managed inventory for hospital pharmaceutical supply - Krichanchai, Sineenart; MacCarthy, Bart L. (Emerald, 2017)
The study investigates Vendor Managed Inventory (VMI) for the supply of medicines between distributors and hospitals to identify factors that may affect VMI adoption. Multiple case studies are conducted involving five organizations (three hospitals, one distributor, and one manufacturer/ supplier). Four dyadic relationships are identified. Triangulation techniques are used in data collection, including interviews, site visits and document analysis to enhance reliability and validity. Case studies have been analyzed individually and comparatively. Two types of VMI initiatives – public and private sector - are identified in the supplier/hospital context. The public sector supplier focuses on improving service level while the private sector supplier seeks to strengthen relationships with key customers. Hospital characteristics, including the type of hospital, top management perspectives, and the hospital’s willingness to share information, are critical in decisions on VMI initiation or termination. Relatively stable demand products are preferred for a VMI approach. Hospitals may perceive risks in VMI adoption for medicines as it involves relinquishing control of critical supplies and may result in ‘lock-in’ with a particular supplier. The paper provides supply side and demand side perspectives on VMI adoption in an important sector. It highlights the need for greater understanding of the perceived and actual risks in VMI from the perspective of both the hospital and the supplier and for much clearer advice on which pharmaceutical products are appropriate for VMI control in a hospital context. VMI is advocated as being beneficial in many supply contexts. However, it may be challenging to implement. This study identifies a range of factors that affect the adoption of VMI in hospital pharmaceutical supply chains. The cases have been conducted in one country, which may affect the generalization of the findings. Wider empirical evidence from other countries in both developed and less developed regions will be beneficial.